Optimal selection of specimens for metagenomic next-generation sequencing in diagnosing periprosthetic joint infections - Tan, Jun; Wu, Lingxiao; Zhan, Lijuan; Sheng, Minkui; Tang, Zhongxin; Xu, Jianzhong; Ma, Haijun (Frontiers in Cellular and Infection Microbiology, 2024)
This study aimed to assess the diagnostic value of metagenomic next-generation sequencing (mNGS) across synovial fluid, prosthetic sonicate fluid, and periprosthetic tissues among patients with periprosthetic joint infection (PJI), intending to optimize specimen selection for mNGS in these patients.This prospective study involved 61 patients undergoing revision arthroplasty between September 2021 and September 2022 at the First Affiliated Hospital of Zhengzhou University. Among them, 43 cases were diagnosed as PJI, and 18 as aseptic loosening (AL) based on the American Musculoskeletal Infection Society (MSIS) criteria. Preoperative or intraoperative synovial fluid, periprosthetic tissues, and prosthetic sonicate fluid were collected, each divided into two portions for mNGS and culture. Comparative analyses were conducted between the microbiological results and diagnostic efficacy derived from mNGS and culture tests. Furthermore, the variability in mNGS diagnostic efficacy for PJI across different specimen types was assessed.The sensitivity and specificity of mNGS diagnosis was 93% and 94.4% for all types of PJI specimens; the sensitivity and specificity of culture diagnosis was 72.1% and 100%, respectively. The diagnostic sensitivity of mNGS was significantly higher than that of culture (X 2 =6.541, P=0.011), with no statistically significant difference in specificity (X 2 =1.029, P=0.310). The sensitivity of the synovial fluid was 83.7% and the specificity was 94.4%; the sensitivity of the prosthetic sonicate fluid was 90.7% and the specificity was 94.4%; and the sensitivity of the periprosthetic tissue was 81.4% and the specificity was 100%. Notably, the mNGS of prosthetic sonicate fluid displayed a superior pathogen detection rate compared to other specimen types.mNGS can function as a precise diagnostic tool for identifying pathogens in PJI patients using three types of specimens. Due to its superior ability in pathogen identification, prosthetic sonicate fluid can replace synovial fluid and periprosthetic tissue as the optimal sample choice for mNGS.